Strength of Blended Cement Mortar Containing Palm Oil Fuel and Eggshell Ashes - Jamellodin, Zalipah; Nor Azhar, Norazreen; Arif Jamaly, Mohamad; A. Majid, Masni; Salleh, Norhafizah; Azlina Abdul Hamid, Noor; Ismail, Noorli; Hani Adnan, Suraya; Nadhirah Abdul Rashid, Nur (International Journal of Engineering and Technology, 2018)
This study investigated characteristics strength of blended cement mortar containing palm oil fuel ash (POFA) and eggshell powder (ESP). POFA and ESP were easily sourced from palm mills and bakeries. POFA was dried in the oven at 105-110 Â°C for 24 hours while ESP was sun-dried. Cement in mortar partially substitute 20% by weight of cement by both ashes to form their cement blends. POFA is divided into two groups which is unground POFA (UPOFA) and ground POFA (GPOFA). A total of 36 mortar cube of 100mm x 100mm x 100 mm was tested at curing ages of 28 days for determination of compressive strength. The recommended mix design of 1: 3 and the 0.5 water / cement ratio was adopted referred to the BS EN 196-1: 2015 standard specification. Then, the XRD testing was conducted for the highest compressive strength value of blended mortar and control mortar. The results show that the blended mortar C80GP16E4 gives the highest compressive strength of 21.3 MPa which increases by 6.5% compared to the control mortar, 20 MPa. For mortars containing only 20% replacement of UPOFA or GPOFA, they give 17.4 MPa and 14.3 MPa compressive strength respectively. An increase of 21% for GPOFA. This is due to the high fineness of POFA providing more surface area that filled the voids between cement and aggregate. The paper concludes that POFA and ESP separately or as a binary blends can be adopted as a partial substitute for cement in mortar production but must not exceed 20% cement weight.Â Â